Assessing biochar applications and repeated Brassica juncea L. production cycles to remediate Cu contaminated soil. (June 2018) - Gonzaga, Maria Isidoria Silva; Mackowiak, Cheryl; Quintão de Almeida, André; Wisniewski, Alberto; Figueiredo de Souza, Danyelle; da Silva Lima, Idamar; Nascimento de Jesus, Amanda
Abstract: Copper contamination and toxicity in soils is a worldwide problem, especially in areas where copper-based fungicides are applied. Indian mustard ( Brassica juncea L.) plants are used in phytoremediation and are also edible crops commonly cultivated in organic agricultural areas. Application of biochar to Cu contaminated soils may reduce Cu availability and uptake, thereby allowing for greater Indian mustard production. A (3 × 2) + 1) experiment in a randomized complete block design was used to evaluate the effect of three different biochars (coconut shell, orange bagasse and sewage sludge) and two application rates (30 and 60 t ha −1 ) on Cu uptake by Indian mustard during three successive growth cycles and Cu immobilization in soil, under greenhouse conditions. Coconut husk biochar did not influence available soil Cu; however, its presence increased shoot Cu uptake by 117% and 38% in the two last growth cycles. Orange bagasse biochar, at the 60 t ha −1 application rate, reduced Cu availability, but it was not effective in reducing Cu uptake. Sewage sludge biochar did not affect Cu availability and caused an approximated 100% increase in shoot Cu uptake at the highest application rate. Therefore, the orange bagasse biochar is the most effective whereas the sewage sludge biochar is the least in Cu immobilization. None of the biochars was shown to be suitable as soil amendment to reduce the uptake of Cu by Indian mustard. However, coconut shell and sewage sludge biochar can be effectively applied to soil as an auxiliary tool to remediate Cu-contaminated soils. Highlights: Biochar immobilizes Cu in a contaminated Ultisol. Cu immobilization was higher in biochar from coconut shell and orange bagasse than from sewage sludge. All biochars improved plant yield. Biochar did not prevent Cu uptake by Brassica plants.